Short track vs hockey helmets: investigating impact attenuation properties of helmets in two skating sports - Aponte, D.; Leclerc, S.; Pearsall, D. (British Journal of Sports Medicine, 2021)
Background: Certification standards governing short track (ST) helmets only require high velocity impacts be tested. Rotational acceleration and low velocity impacts are mechanisms of injury which are known to cause concussion. Conversely, ice hockey (IH) helmet certification require low velocity impacts in addition to high velocity impacts, and have been designed to mitigate both impact velocities. Objective: To compare the impact attenuation characteristics between ST and IH helmets, in both high and low velocity impacts. Design: Two-group experimental design. Setting: Impacts were performed in laboratory under controlled conditions. Helmets were impacted at two impact velocities (high and low; 4.5m/s and 2.4m/s respectively) and four impact locations (rear, rear boss, side and front boss). This was performed using a linear impactor device and the Hybrid III surrogate headform and neck. Patients (or Participants:) 5 different helmet models; 3 ST models and 2 IH models. Interventions (or Assessment of Risk Factors): Assessment of ST and IH helmet impact attenuation under various conditions. Main Outcome Measurements: Peak linear and rotational acceleration; Head Injury Criterion (HIC) and Brain Injury Criterion (BrIC). Results: Between-groups ANOVA for linear [Low F(1,27) = 10.7, p<0.05, h2 = 0.284; High = F(1,24) = 5.8, p<0.05, h2 = 0.195] and rotational [Low F(1,27) = 15.8, p<0.05, h2 = 0.370; High = F(1,24) = 8.1, p<0.05, h2 = 0.251] accelerations yielded statistically significant differences with large effect sizes for all impact locations in both impact velocities. One-way between-helmet ANOVAs and post-hoc Bonferroni revealed impact attenuation performance hierarchy: IH 2 > IH 1 > ST 3 > ST 1 > ST 2. Between-groups ANOVA revealed statistical differences for HIC [Low F(1,27) = 14.1, p<0.05, h2 = 0.344; High = F(1,24) = 7.6, p<0.05, h2 = 0.241]. BrIC results were mixed. Conclusions: Results suggest that these IH helmets are better at attenuating both impact velocities than this group of ST helmets. Interestingly, the largest effect sizes were observed in the low-velocity impacts.